Anticoagulation endpoints with clinical implementation of warfarin pharmacogenetic dosing in a real‐world setting: A proposal for a new pharmacogenetic dosing approach. Issue 5 (29th December 2016) - Arwood, MJ; Deng, J; Drozda, K; Pugach, O; Nutescu, EA; Schmidt, S; Duarte, JD; Cavallari, LH
Abstract : Achieving therapeutic anticoagulation efficiently with warfarin is important to reduce thrombotic and bleeding risks and is influenced by genotype. Utilizing data from a diverse population of 257 patients who received VKORC1 and CYP2C9 genotype‐guided warfarin dosing, we aimed to examine genotype‐associated differences in anticoagulation endpoints and derive a novel pharmacogenetic nomogram to more optimally dose warfarin. We observed significant differences across patients with 0, 1, or ≥2 reduced‐function VKORC1 or CYP2C9 alleles, respectively, in time to achieve therapeutic international normalized ratio (INR) (7.8 ± 5.8, 7.2 ± 4.7, and 5.4 ± 4.6 days, P = 0.0004) and mean percentage of time in therapeutic range in the first 28 days (22.2, 27.8, and 32.2%, P = 0.0127) with use of existing pharmacogenetic algorithms. These data suggest that more aggressive dosing is necessary for patients with 0 to 1 VKORC1/CYP2C9 variants to more efficiently achieve therapeutic anticoagulation. Herein, we provide a novel kinetic/pharmacodynamic‐derived dosing nomogram optimized for a heterogeneous patient population.